Hardness Test Analysis on ST 37 Steel Plate Material and Aluminum Using the Brinell Test Method - Sinaga, Franklin Taruyun Hudeardo; Boangmanalu, Eka Putra Dairi; Pratama, Angga Bahri; Saragi, Jandri Fan HT; Al Qadry; Sahat (PT FORMOSA CENDEKIA GLOBAL, 2023)
One of the most frequently used methods of material testing is hardness testing. The aim of conducting research on material hardness is to determine the hardness value of the material specimens tested, namely ST 37 steel plate and aluminum plate. The test method is to use the Brinell hardness test where the values ​​obtained during testing are from the force load, indenter diameter and pressure trace diameter and the pressure time that has been determined. By using testing tools such as hardness tester, mechanical caliper, indenter, flat file, stopwatch. And the materials used are ST 37 steel plate, aluminum plate and sandpaper. From the test results obtained we can calculate the Brinell hardness value of the test material. The value from the calculation of test data where the highest hardness value using the Brinell method (BHN) for ST 37 steel plate material is 256.992. Meanwhile, the highest hardness value using the Brinell method (BHN) for aluminum plate material is 55,182.